Perambahan Hutan dan Kerusakan Lingkungan Hutan Cagar Alam di Pengunungan Cycloop Distrik Sentani Tengah Kabupaten Jayapura Propinsi Papua - , Pestigridis Monim, ST. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Cycloop mountains nature reserve area as one of the protected areas conservation or protected has a function which is very important. Factors that affect the environmental damage caused by activities of forest encroachment in CAP Cycloop. Activities of the community in the form of appropriation of forests by changing into the fields, affect the environment function changes a previously as a nature reserve area. To that end this research aims: (1) Examine factors cause the occurrence of environmental damage, the community and the region Hinekombe Lemongrass reserves the Cycloop. (2) How land use activities by forest communities (based on respondent community Hinekombe and Lemongrass), in the mountainous nature reserve Cycloop?. (3) Drafting an alternative landing as a result of environmental management strategies of forest encroachment by community activity Hinekombe and Lemongrass, in the mountainous nature reserve Cycloop. Research method used is descriptive method. The population of this study was Sentani District Community Tenggah nature reserve at the foot of the mountains Cycloop by 20 respondents. Respondents were selected was head of the family, the affected forest encroachment. Based on data from Sentani District monograph in 2010, it is known that the number of residents in the district as many as 257 families Sentani. Community leaders who were interviewed to obtain data supporting as many as 3 people, 5 villagers comparison of new and old residents in the village Hinekombe and Lemongrass. Analysis of the data used is the analysis of qualitative and quantitative data. The results are known factors causing environmental damage Cycloop mountain nature reserve, namely: lack of public knowledge about the nature reserve. Erosion of indigenous communities Sentani, factors of development is quite rapid, less wise land use. Many found environmentally destructive shifting cultivation, where the factor of lack of education to be one of the triggers of environmental vandalism Cycloop mountain nature reserve by the public. Floods and landslides are environmental impact of farming around the Cycloop mountain nature reserve, this is due to lack of public awareness in managing land wisely. In the community development needs to be a management strategy, both short-term management strategies, medium term, and long-term management strategy, to be adjusted to the presence and state of society today. To support the ultimate goal rather than management, the mountainous nature reserve Cycloop as conservation zones.